TRAÇADO URBANO E SUA INFLUÊNCIA NO MICROCLIMA: UM ESTUDO DE CASO EM CENTRO HISTÓRICO - Franco, Fernanda Miguel; Nogueira, Marta Crista de Jesus Albuquerque; Pinto Júnior, Osvaldo Borges; Biudes, Marcelo Sacardi; Nogueira, José de Souza (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707697 Cuiabá is a city in central-western Brazil, its colonization occurred in the early eighteenthcentury and its urban design features architectural features of the influence of its Portuguesecolonizers. The design of empirical layout of the city, despite not having as premise the conceptsof bioclimatology in many practice takes advantage of the weather to create an architectureadapted to the local climate. The objective of this study is to analyze in order to identify characteristics related to urban design in bioclimatology Stroke vernacular city of Cuiabá,discussing its consequences in urban comfort and city planning in the pedestrian scale. For thisiconographic surveys were conducted in the historic center, together with a literature search inthe area of urban climate that involves the locality studied and a survey of micrometeorologicaldata. As a result the paper ends by identifying possible actions to help cities become moreadapted to the local climate characteristics.